Increase of serum corticol levels in response to stress, interleukin-6 (IL-6) levels and adhesion degrees after laparotomy and laparoscopy (experimental research in rabbit which performed ileum abrasion) - Ananggadipa J (RSUP Dr. Kariadi, 2016)
Background : Peritoneal adhesion occurs in more than 50 - 97% of cases of transperitoneal surgery whisch is still an issue of high morbidity and mortality. Minimally invasive surgery has a significantly lower incidence of postoperative peritoneal adhesions. Peritoneal adhesions involve many mediators such as IL-8, TNF-±, IL-1², IL-6, TGF-². Laparoscopy minimize tissue trauma so that the levels of ACTH, cortisol, prolactin, noradrenaline and adrenaline are lower. This study seeks to prove the correlation between the type of abdominal surgery with peritoneal adhesion levels mediated by the increase in cortisol levels and the increase in IL-6 levels. Methods : A laboratory experimental research using twelve male New Zealand rabbits which divided into two groups was done. The treatments were laparotomy and laparoscopy where the terminal ileum abrasion was done. Blood cortisol levels were taken before treatment and 6 hours after treatment. Levels of IL-6 levels were tht aken from the peritoneal fluid samples on 7 day after treatment. Examination using ELISA method. Assessment of the adhesion degree was done based on macroscopic criteria. Results : The level of serum cortisol, peritoneal fluid IL-6 and intra peritoneal adhesion degrees in the laparotomy group is significantly higher than the laparoscopy group (p=0.021, p<0.001, p=0.002). There were strongly positive and significant correlation between the levels of cortisol and IL-6 (p=0.001 and r=0.827). There were strongly positive and significant correlation between the levels of IL-6 and the degrees of adhesion (p<0.001 and r=0.878). Conclusion : The level of serum cortisol, peritoneal fluid IL-6 and intra peritoneal adhesion are higher in laparatomy compared with laparoscopy.